ANALISIS PERENCANAAN PERSEDIAAN BATUBARA FX DENGAN METODE MATERIAL REQUIREMENT PLANNING - Muhammad Arief; Supriyadi Supriyadi (Jurnal Manajemen Industri dan Logistik, 2017)
A company often has difficulty in controlling raw materials,it could be surplus or minus. Preventing these problem,we made a problem solving. Material needs planning is made for efficient and effective materials application  in the execution of work, so the problems because of material is avoided.this  research purpose is planning  and controlling raw material and supplier selection by Material Requirement Planning (MRP) method. Material Requirement Planning is a method for determining materials or components which  make or buy, how much it is needed and when it is needed. The result using the calculation by MRP method show Fix Period Requirement (FPR) is the best method, because the calculation of Fix Period Requirement method got the lowest total cost that is  Rp.18,722,190,090, -.FPR is obtained a profit about Rp. 6.096.088.915,00 or about 25% more efficient than the method applied company.